Selective Toxicity Effect of Fatty Acids Omega-3, 6 and 9 Combination on Glioblastoma Neurons through their Mitochondria - Seydi, Enayatollah; Sadeghi, Hadiseh; Ramezani, Maral; Mehrpouya, Leila; Pourahmad, Jalal (Drug Research, 2021)
Glioblastoma (GBM) is one of the most common malignant tumors of the central nervous system that occurs in the brain and is a deadly disease. Despite the different approaches to the treatment of this malignancy, the discovery of new compounds with anti-cancer effects seems necessary. In this study, the selective toxicity effects of omega 3, 6 and 9 combinations on mitochondria isolated from U87MG human glioma cells and also human embryonic kidney 293 cells (HEK293) as normal control were investigated. The results indicated that the omega 3, 6 and 9 combinations significantly reduced succinate dehydrogenase (SDH) activity only in mitochondria isolated from U87MG human glioma cells. Additionally, exposure of mitochondria isolated from U87MG human glioma cells to this combination was associated with a selective increase in the level of reactive oxygen species (ROS), the collapse of the mitochondrial membrane potential (MMP), mitochondrial swelling and cytochrome c release. However, these effects were not observed in mitochondria isolated from HEK293 cells (as a normal group). According to results, it is proposed that the combination of omega 3, 6 and 9 could induce toxicity in U87MG human glioma cells through their mitochondria. This combination can be helpful as a complementary therapy in patients with GBM.
Keywords: Anticancer; Reactive Oxygen Species; Oxidative Stress; Apoptosis; Cytochrome c